Rapid kinetics of iron responsive element (IRE) RNA/iron regulatory protein 1 and IRE-RNA/eIF4F complexes respond differently to metal ions - Khan, Mateen A. (Oxford University Press, 2014)
Metal ion binding was previously shown to destabilize IRE-RNA/IRP1 equilibria and enhanced IRE-RNA/eIF4F equilibria. In order to understand the relative importance of kinetics and stability, we now report rapid rates of protein/RNA complex assembly and dissociation for two IRE-RNAs with IRP1, and quantitatively different metal ion response kinetics that coincide with the different iron responses in vivo. k(on), for FRT IRE-RNA binding to IRP1 was eight times faster than ACO2 IRE-RNA. Mn(2+) decreased k(on) and increased k(off) for IRP1 binding to both FRT and ACO2 IRE-RNA, with a larger effect for FRT IRE-RNA. In order to further understand IRE-mRNA regulation in terms of kinetics and stability, eIF4F kinetics with FRT IRE-RNA were determined. k(on) for eIF4F binding to FRT IRE-RNA in the absence of metal ions was 5-times slower than the IRP1 binding to FRT IRE-RNA. Mn(2+) increased the association rate for eIF4F binding to FRT IRE-RNA, so that at 50 µM Mn(2+) eIF4F bound more than 3-times faster than IRP1. IRP1/IRE-RNA complex has a much shorter life-time than the eIF4F/IRE-RNA complex, which suggests that both rate of assembly and stability of the complexes are important, and that allows this regulatory system to respond rapidly to change in cellular iron.